ADIPOGENESIS TUMBUH KEMBANG ADIPOSIT - Wangko, William S.; Wangko, Sunny (Jurnal Biomedik : JBM, 2010)
Abstract: Adipogenesis is defined as the growth and development of adipose tissue, which includes proliferation of adipose tissue cells and differentiation of these cells to become mature adipocytes. It is assumed that adipocytes are derived from multipotent messenchymal cells, fibroblasts, and resident adipocyte precursors in adipose tissues. Besides having genetic, nutritional, hormonal, and environmental factors, the progress of adipogenesis is influenced by angiogenesis and a variety of modulators (stimulators and inhibitors). Imbalance of all of these will trigger the formation of  excessive adipose tissues, the result being obesity and its co-morbids. Adipose tissues can be used in accelerating  the healing process of old wounds, revascularization of ischemic tissues, and in ongoing research as sources of cardiomyocytes in myocardial infarction. Key words: adipogenesis, adipocyte, proliferation, differentiation   Abstrak: Adipogenesis merupakan proses tumbuh kembang jaringan adiposa yang meliputi proliferasi sel jaringan adiposa dan diferensiasinya menjadi adiposit dewasa. Sel adiposit diduga dapat berasal dari sel mesenkim multipoten, fibroblas, dan sel prekursor adiposit di dalam jaringan adiposa yang bertahan sepanjang hidup. Selain faktor genetik,  nutrisi, hormonal dan lingkungan, perlangsungan adipogenesis juga dipengaruhi oleh angiogenesis serta berbagai modulator, baik yang bersifat stimulasi maupun inhibisi. Ketidakseimbangan yang terjadi pada kerja faktor-faktor tersebut dapat memicu pembentukan jaringan adiposa yang berlebihan, yang berakibat terjadinya obesitas berserta komorbidnya. Pemanfaatan jaringan adiposa telah dilakukan pada beberapa hal, antara lain mempercepat penyembuhan luka lama dan revaskularisasi jaringan iskemik. Walaupun masih dalam taraf penelitian, sel-sel jaringan adiposa telah dipertimbangkan sebagai sumber kardiomiosit pada infark jantung. Kata kunci: adipogenesis, adiposit, proliferasi, diferensiasi